PRIMER REGISTRO DE AULACIDAE (HYMENOPTERA, EVANIOIDEA) DE URUGUAY CON DESCRIPCIÓN DE UNA NUEVA ESPECIE DE Aulacus - Perioto, Nelson Wanderley; Lara, Rogéria Inês Rosa; Turrisi, Giuseppe Fabrizio (Boletín de la Sociedad Zoológica del Uruguay, 2020)
The presence of the parasitoid wasp family Aulacidae (Hymenoptera, Evanioidea) in Uruguay is documented for the first time. Two species are recorded, Aulacus castiglionii Perioto, Lara, Turrisi, sp. nov., and Pristaulacus ambiguus (Schetterer, 1890).